Anatomical and Radiological assessment of Acromion morphology and morphometry and its clinical significance in in shoulder impingement syndrome - AKHIL, PALLE SREE; Philip, X. Chandra; Philip, Lokesh; Nancy, Anitha; Palagani, Akshay (International Journal of Psychosocial Rehabilitation, 2020)
To record the Radiological parameters, Anatomical assesment of morphology & morphometric parameters of the acromion process of scapula.Co-relating the values of present study with various parameters obtained from other studies.To study the bony abnormalities associated with impingement syndrome and to measure the length of subacromian space using magnetic resonance imaging.Subacromial space is a gap between the non elastic coracoacromial arch and the head of the humerus.The space is filled by subacromial bursa, supraspinatus tendon and biceps tendon. Raising the arm in activities like combing of the hair, narrows the subacromial space. The space is further narrowed by anatomical abnormalities of acromion process of scapula resulting in impingement which is a disorder of shoulder joint . Radiological parameters, and anatomical parameters of the acromion process are essential in diagnosing the pathogenesis of rotator cuff disease and shoulder impingement syndrome.The study was done at Department of Anatomy & Department of Radiology , MGMC & RI on 80 dry unpaired scapula without any external deformities and age and sex of these scapulas were unknown. Study also included 30 Magnetic resonance Imaging scans (MRI) of patients with history of shoulder pain suggestive of rotator cuff pathology.The thickness of the acromion process, acromial breadth, acromial length, acromio-glenoid distance and acromio-coracoid distance were measured with measuring tape and also by using sliding vernier caliper .Various shapes acromion process were also noted.The bony abnormalities were noted and the length of subacromial space were also measured by MRI.Out of the 80 dry scapulas of unknown age and sex , various shapes of the scapula that were observed were as follows Curved type (type 11) was seen in 58% of scapula. Hooked type ( type 111) was seen in 37% of cases followed by Flat type (type1) acromion process in 5% of cases.The mean breadth and length of the acromion process were 24.03mm and 43.6mm , respectively. The mean anterior acromial thickness is 6.94mm, the mean coracoacromial distance is 28.9mm, the mean acromioglenoid distance is 27.35 mm.